DETERMINANTS OF RETAIL CUSTOMER SATISFACTION: A STUDY OF ORGANIZED RETAIL OUTLETS IN ERNAKULUM, KERALA - LIGO KOSHY AND S. JOHN MANOHAR (International Journal of Multidisciplinary Management Studies, 2014)
Retailing consists of the sale of goods from a fixed location, such as a department store or kiosk, in small or individual lots for direct consumption by the purchaser. Some retailing businesses sells a combination of goods and services. Since the last decade, the field of retailing has experienced significant changes. Retailing in India is one of the pillars of its economy and accounts for 14 to 15 percent of its GDP. The Indian retail market is estimated to be US$ 500 billion and one of the top five retail markets in the world by economic value. India is one of the fastest growing retail markets in the world, with 1.2 billion people. As of 2013, India's retailing industry was essentially owner manned small shops. In 2010, larger format convenience stores and supermarkets accounted for about 4 percent of the industry, and these were present only in large urban centers. India's retail and logistics industry employs about 40 million Indians (3.3% of Indian population). Organized retailers, defined here as a store that offers a mix of tangible goods and services, are experiencing a philosophical shift from a profit centered objective to a customer centered, relationship oriented objective. One strategic alternative to differentiate themselves from other retailers of similar product lines is a focus on high level of customer service and customer satisfaction. By satisfying customer through high quality service, business firms not only retain their current customers, but also increased their market share. The current study is aimed to explore the components of retail customer satisfaction and also investigate the relationship between each of the retail customer satisfaction components and customers satisfaction level. Study also aims at ranking the factor of satisfaction and to study the motivating features for the consumers to visit organized retail outlets. This study will help the various organized retail outlets for identifying the need of consumers and improve the image of organized retailers